Dielectric properties and ac conductivities of Bi 1− x Sm x FeO 3 ceramics - Kallaev, Suleyman Nurulislanovich; Alikhanov, Ruslan; Bormanis, Kārlis; Sadykov, S. A.; Kalvāne, Anna (Taylor and Francis Ltd., 2019)
Dielectric permittivity, dielectric losses and ac-conductivity of polycrystalline Bi1−xSmxFeO3 (x = 0; 0.05; 0.1; 0.15; 0.2) are measured in the frequency range 1 kHz–10 MHz and in the temperature range 25–600 °C. Anomalies have been observed at the 200 °C, 300 °C and at the Néel temperature. It has been demonstrated that doping with Sm has enhanced the dielectric properties and increased conduction in the frequency region <1 MHz. At high frequency (>1 MHz) and at a certain temperature Tm, depending on the composition Bi1−xSmxFeO3, the conductivity reaches a maximum. The results are discussed with reference to the model of correlated barrier hopping.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; BiFeO3 ceramics; dielectric properties; conductivity